The progress of epigenetics in the development and progression of non-alcoholic fatty liver disease - Fen Xu; Wanrong Guo (Liver Research, 2020)
Non-alcoholic fatty liver disease (NAFLD) has become a global epidemic nowadays. Although the pathogenesis of NAFLD remains to be uncovered, it is highly correlated with the changing of environment as other metabolic diseases. Epigenetics is the study on the differences of gene expression not caused by the changes in DNA sequencing. The epigenetics is considered to link the environment factors and the onset and development of NAFLD. As an increasing number of researches on epigenetics have emerged in recent years, our understanding of how epigenetic factors take part in the pathogenesis of NAFLD has been improved. This article reviews the recent studies on important epigenetic factors contributing to the progression of NAFLD including the DNA methylation, modification of histones and non-coding RNAs. It may give us a hint to discover novel diagnosis methods and drug targets for NAFLD.